Palaearctic Agromyzidae collected from Bezzi and kept in the Natural History Museum of Milan (Bollettino di zoologia agraria e bachicoltura, 2024)
The specimens of Agromyzidae collected from Bezzi and kept in the Natural History Museum of Milan were examined. The specimens in question are belonging to 79 species, 15 of them are new for Italy and one, Phytomyza achilleaececis, gall forming on Achillea ligustica, is described for the first time.